Harmoni Beragama Dan Pencegahan Konflik: Perspektif Moderasi Menurut Al-Qur’an Dan Alkitab - Zuhriyandi, Zuhriyandi (Moderatio: Jurnal Moderasi Beragama, 2023)
In the era of globalization which accelerates encounters between cultures and religions, the challenge of maintaining religious harmony is increasingly urgent. Religious conflicts arising from differences in beliefs can pose a serious threat to the peace and stability of society. Therefore, this research aims to explore the concept of religious harmony and analyze the role of moderation from the perspective of the Koran and the Bible in preventing religious conflict. Through a comparative approach to the Koran and the Bible, this research considers the views of moderation contained therein as a guide for peaceful coexistence. By understanding the values of religious moderation, it is hoped that it will be possible to formulate concrete strategies to promote inter-religious harmony and prevent conflict. The research method involves analyzing the texts of the Koran and the Bible with a qualitative approach. This research will analyze the texts of the Koran and the Bible to identify the values of moderation which can be the basis for religious harmony. It is hoped that the results of this research will provide a deeper understanding of the contribution of moderation in major religions such as Islam and Christianity to religious harmony and conflict prevention. Thus, it is hoped that this research can make a positive contribution in building a harmonious and peaceful society amidst religious diversity.